A case study of offshore wind turbine positioning optimization methodology using a novel multi-stage approach - Xiaosen Xu; Lin Du; Zhongyu Zhang; Jiayang Gu; Yihan Xing; Oleg Gaidai; Peng Dou (Frontiers in Marine Science, 2022)
This investigation maximize the annual energy production (AEP) of a wind farm’s layout at a specific site using a novel multi-stage approach. The downstream wind turbines’ energy production decreases due to the reduced wind speed and turbulence created by the upstream wind turbines’ wakes. The wake interference from wind turbines causes the reduction of overall power efficiency. This paper provides a novel multi-stage strategy for the optimal layouts generated by heuristic algorithms to address this problem. A comparison of the proposed multi-stage approach to previous optimization algorithms is presented to demonstrate its efficiency using three referenced cases and one potential wind farm in the Gulf of Maine. The results demonstrate that applying the proposed multi-stage approach increases AEP and decreases computational time compared to previous research and optimization algorithms, which is crucial for large-scale offshore wind farm layout design and optimization.